THE IMPLEMENTATION OF READING COMPREHENSION DURING INTERNSHIP PROGRAM - Alya Rahayu Gunardi; Yessy Purnamasari (UICELL, 2021)
Internship is essential for polytechnic students to apply their knowledge on a particular subject. In applying the knowledge, students are required to do internships at offices that are in line with their study program. In this case, reading comprehension becomes the main focus of the application in doing the internship. This study aims to describe the implementation of reading comprehension during the internship program at the international relation office of a public university in Bandung. The reading comprehension is applied in three activities: collecting information on exchange programs, searching for the information on short programs, as well as gathering information on important dates of university’s partners. Data collection methods applied in this study are observation and library study. This study shows that reading comprehensions such as scanning, skimming, and making interpretations are highly utilized in the tasks: seeking essential information in universities official websites, checking the availability of short programs for foreign students, and finding the differences on important dates among countries university’s partners. These works are important for both interns to improve and apply the knowledge and the university to get the updated information on global education and mobility. Keywords: reading comprehension, internship, polytechnic, international office